Burn injury and gender inequity: epidemiological insights and social determinants - Sahu, Ranjit K.; Sahu, Sabita; Jena, Harapriya; Aisureya, J. B.; Sahu, Sachidananda; Barik, Umesh; Saha, Sanjana; Sahu, Pragati; Pati, Hemalata; Sahu, Tapaswini; Mohanty, Jasmine (International Journal Of Community Medicine And Public Health, 2025)
Burn injuries pose a significant global health burden, with the overwhelming majority of deaths around 90% occurring in low and middle-income countries (LMICs). India alone reports an estimated 6–7 million burn cases annually, ranking among the highest globally. Women are disproportionately affected due to unsafe cooking practices, flammable traditional clothing, use of hazardous fuels, and gender-based violence. Socio-cultural norms and economic constraints further increase vulnerability and delay timely access to care. This review explores the gendered dimensions of burn injuries in India, including epidemiology, risk factors, healthcare access, psychosocial impact, and policy responses. A thorough review of the literature was carried out using PubMed, Google Scholar, and the World Health Organization (WHO) Global Health Library, along with grey literature from government and policy sources. Data were thematically synthesized into key domains to identify patterns in injury causation, severity, treatment gaps, and intervention strategies. Evidence indicates that women experience more severe burns and higher mortality even with smaller burn surface areas, largely due to delayed care, financial barriers, and gender bias in healthcare delivery. Intentional burns resulting from domestic violence, dowry-related harassment, and self-immolation substantially contribute to the burden, although misclassification of such cases is common. Psycho social stigma, insufficient mental health support, and limited rehabilitation services further hinder recovery and social reintegration. Addressing these disparities requires gender-responsive approaches, including disaggregated surveillance, integration of violence screening into burn care, strengthened rehabilitation services, community-based prevention, and public awareness initiatives. Legal protections and training healthcare providers in gender-sensitive care are critical to reducing inequities. A coordinated, multi-sectoral strategy is essential to ensure equitable outcomes and mitigate the disproportionate impact of burn injuries on women in India.